Enhancing Preschool Children’s ToothbrushingIndependence Through Video TutorialEducation: A Study on Knowledge and Practices - Silvia Prasetyowati; Meyvilia Yunardi Saputri; Isnanto (International Journal of Advanced Health Science and Technology, 2025)
Preschool children represent a critical developmental stage in which foundational health behaviors, includingtoothbrushing, begin to form. Although most Indonesian children aged ≥3 years brush their teeth daily, only a small proportiondo so correctly, resulting in persistently high rates of dental and oral health problems. This study addresses the problem oflow toothbrushing knowledge and inadequate brushing practices among preschool children. The aim of this research was toevaluate the effectiveness of video tutorial–based dental health education in enhancing preschool children’s independence,knowledge, and practical skills in toothbrushing. A pre-experimental study with a pre-test–post-test control group design wasconducted among 38 preschool children enrolled in Putra Harapan Kindergarten and Dewi Sartika Kindergarten, Tuban.Participants were divided into an experimental group receiving video tutorial education and a control group receiving verbaleducation only. Data on knowledge and toothbrushing practices were collected using structured observation sheets, andanalyzed using the Wilcoxon signed-rank test and Mann–Whitney U test. The results demonstrated a significant improvementin both knowledge and toothbrushing practices in the experimental group after 21 days of intervention (p < 0.001). In contrast,the control group showed no significant changes in either outcome. Between-group comparisons further indicated that videotutorial education was significantly more effective than verbal instruction in increasing correct toothbrushing knowledge andpractices (p < 0.001). In conclusion, video tutorial media is an effective educational tool for enhancing preschool children’sindependence in toothbrushing. Its engaging visual format improves comprehension and encourages children to imitate properbrushing movements, leading to better oral hygiene behaviors. The findings support the integration of video-based learninginto early childhood dental health programs and future studies with longer follow-up periods are recommended to assesslong-term behavioral retention.